Role of a Real-Time TDM-Based Expert Clinical Pharmacological Advice Program in Optimizing the Early Pharmacokinetic/Pharmacodynamic Target Attainment of Continuous Infusion Beta-Lactams among Orthotopic Liver Transplant Recipients with Documented or Suspected Gram-Negative Infections - Milo Gatti; Matteo Rinaldi; Cristiana Laici; Antonio Siniscalchi; Pierluigi Viale; Federico Pea (MDPI AG, 2023)
(1) Objectives: To describe the attainment of optimal pharmacokinetic/pharmacodynamic (PK/PD) targets in orthotopic liver transplant (OLT) recipients treated with continuous infusion (CI) beta-lactams optimized using a real-time therapeutic drug monitoring (TDM)-guided expert clinical pharmacological advice (ECPA) program during the early post-surgical period. (2) Methods: OLT recipients admitted to the post-transplant intensive care unit over the period of July 2021-September 2023, receiving empirical or targeted therapy with CI meropenem, piperacillin-tazobactam, meropenem-vaborbactam, or ceftazidime-avibactam optimized using a real-time TDM-guided ECPA program, were retrospectively retrieved. Steady-state beta-lactam (BL) and/or beta-lactamase inhibitor (BLI) plasma concentrations (Css) were measured, and the Css/MIC ratio was selected as the best PK/PD target for beta-lactam efficacy. The PK/PD target of meropenem was defined as being optimal when attaining a fCss/MIC ratio > 4. The joint PK/PD target of the BL/BLI combinations (namely piperacillin-tazobactam, ceftazidime-avibactam, and meropenem-vaborbactam) was defined as being optimal when the fCss/MIC ratio > 4 of the BL and the fCss/target concentration (CT) ratio > 1 of tazobactam or avibactam, or the fAUC/CT ratio > 24 of vaborbactam were simultaneously attained. Multivariate logistic regression analysis was performed for testing potential variables that were associated with a failure in attaining early (i.e., at first TDM assessment) optimal PK/PD targets. (3) Results: Overall, 77 critically ill OLT recipients (median age, 57 years; male, 63.6%; median MELD score at transplantation, 17 points) receiving a total of 100 beta-lactam treatment courses, were included. Beta-lactam therapy was targeted in 43% of cases. Beta-lactam dosing adjustments were provided in 76 out of 100 first TDM assessments (76.0%; 69.0% decreases and 7.0% increases), and overall, in 134 out of 245 total ECPAs (54.7%). Optimal PK/PD target was attained early in 88% of treatment courses, and throughout beta-lactam therapy in 89% of cases. Augmented renal clearance (ARC; OR 7.64; 95%CI 1.32-44.13) and MIC values above the EUCAST clinical breakpoint (OR 91.55; 95%CI 7.12-1177.12) emerged as independent predictors of failure in attaining early optimal beta-lactam PK/PD targets. (4) Conclusion: A real-time TDM-guided ECPA program allowed for the attainment of optimal beta-lactam PK/PD targets in approximately 90% of critically ill OLT recipients treated with CI beta-lactams during the early post-transplant period. OLT recipients having ARC or being affected by pathogens with MIC values above the EUCAST clinical breakpoint were at high risk for failure in attaining early optimal beta-lactam PK/PD targets. Larger prospective studies are warranted for confirming our findings.